Política de turismo e desenvolvimento local: avaliação do PRODETUR/NE I no Município de Paraipaba-CE - Barros, Francisco José Leite de (2009)
This research’s theme is centered on the relation between the Public Tourism Politics and the Local Development, having Paraipaba’s county as the focus of the investigation. It was tried to comprehend in which way tourism, being a contradictory activity and appropriated as territory merchandise, would provide development, from the valuation of the local people, having it based on a sustainable model. In this studying case, it was concluded that the tourism induction in the Paraipaba development wasn’t confirmed, reporting the opposite of what was established on the goal of the Program and to what was diffused by speeches of the public governors. There was an excessive concentration of the investments applications on the infrastructure, according to the state macro strategy based on the attraction of foreign investments. The political and administrative discontinuity, the destructuring of the county organ and the staff turnover, reflected on the weakness of the administrative organization and on the county management. It was concluded that the institutional dimension to the local and integrated development of the county is very important for the search of an efficient model of governance.